Informative aspects of vague language - Grasso, Marina (Lenguas Modernas, 2015)
Abstract: This work deals with the analysis of different functions that vague language expresses in informal conversations between young Argentine students, and with the strategic reasons that can lead a speaker to use it. The corpus analysed belongs to the research project Cohesion and coherence in colloquial interaction, (Universidad Nacional de La Plata, Argentina) and it is formed by sixty spontaneous conversations between university students aged 18 to 28. The principles of the Appraisal System were taken as the basis of this study (White 2000, Martin & White 2005, Hood & Martin 2005), immersed in the Systemic Functional Linguistics. Specific bibliography on vague language was also consulted (Channell 1994; Cutting 2007) as well as studies of youth language (Rodríguez González 2002; Stenström and others 2002). The data reveals that the use of vague categories can respond to various reasons: to signal the level of certainty or uncertainty in relation to the information given; to give the idea that what is said should not be taken literally; to establish rapport between the participants taking in mind the shared knowledge and the sense of belonging to a group that the use of a particular expression or word can imply. It isworth mentioning that, contrary to what some authors have claimed, the fragments that include vague language do not necessarily lack information but provide a typeof information that is different from that of similar fragments with more precise language.